2003
DOI: 10.4161/cbt.2.2.237
|View full text |Cite
|
Sign up to set email alerts
|

μ-Calpain Activation in β-Lapachone-Mediated Apoptosis

Abstract: Beta-lapachone (beta-Lap) triggers apoptosis in a number of human breast and prostate cancer cell lines through a unique apoptotic pathway that is dependent upon NQO1, a two-electron reductase. Recently, our laboratory showed that beta-lap-exposed MCF-7 cells exhibited an early increase in intracellular cytosolic Ca(2+) from endoplasmic reticulum stores, and that BAPTA-AM (an intracellular Ca(2+) chelator) blocked these early increases and partially inhibited all aspects of beta-lap-induced apoptosis. We now s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 79 publications
9
78
0
1
Order By: Relevance
“…The role of calpain in mediating PARP1-induced necrosis is somewhat controversial. First proposed by Susin's group as being essential for MNNG-induced AIF translocation and necrosis (Moubarak et al, 2007), several papers have reported a crucial role for calpain in mediating PARP1-induced cytotoxicity (Tagliarino et al, 2003;Vosler et al, 2009;Chiu et al, 2011). This is consistent with findings that chelation of Ca 2+ can abrogate the necrosis elicited by MNNG and b-Lapachone (Tagliarino et al, 2001;Bentle et al, 2006;Chiu et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The role of calpain in mediating PARP1-induced necrosis is somewhat controversial. First proposed by Susin's group as being essential for MNNG-induced AIF translocation and necrosis (Moubarak et al, 2007), several papers have reported a crucial role for calpain in mediating PARP1-induced cytotoxicity (Tagliarino et al, 2003;Vosler et al, 2009;Chiu et al, 2011). This is consistent with findings that chelation of Ca 2+ can abrogate the necrosis elicited by MNNG and b-Lapachone (Tagliarino et al, 2001;Bentle et al, 2006;Chiu et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…In contrast JNK2 knockdown considerably attenuated cell death in response to both compounds suggesting that it is this isoform that plays a causative role in PARP1-mediated necrotic death. -dependent protease calpain as key proximal signals in b-Lapachone-and MNNG-induced necrosis (Tagliarino et al, 2003;Moubarak et al, 2007;Dong et al, 2010). Consistent with this, co-treatment with the Ca 2+ chelating agent BAPTA-AM significantly attenuated the degree of necrotic cell death in response to b-Lapachone and MNNG (Fig.…”
Section: Introductionsupporting
confidence: 67%
“…Western blot analyses of DMSO control or drug-treated MCF-7 cells were done as described (13,16,18). Loading equivalence and transfer efficiency were monitored by Western blot analyses of proteins not altered in cells following h-lapachone exposure as described (13).…”
Section: Methodsmentioning
confidence: 99%
“…The expression of NQO1 in solid cancers is higher than in normal tissues (Belinsky and Jaiswal., 1993), including in carcinoma of the liver (Schlager and Powis, 1990), colon (Smitskamp-Wilms et al, 1995), breast (Schlager and Powis, 1990;Smitskamp-Wilms et al, 1995), brain (Berger et al, 1985), and lung (Schlager and Powis, 1990). In addition, NQO1 has been shown to be an important factor in β-lapachone-induced cell death in many kinds of cancer cells (Pink et al, 2000;Reinicke et al, 2005), including breast cancer (Tagliarino et al, 2003), glioma (Park et al, 2011), and prostate cancer (Pink et al, 2000). In this context, other methods have been examined to increase NQO1 expression or activity in cancer cells (Terai et al, 2009;Tan et al, 2012;Satsu et al, 2012) in order to increase the clinical efficacy of β-lapachone.…”
Section: Mnpces (N)mentioning
confidence: 99%
“…However, it is also possible that β-lapachone induced a small number of DNA strand breaks owing to its ability to produce activated oxygen species (Docampo et al, 1979;Molina Portela and Stoppani, 1996;Molina Portela et al, 1996). β-lapachone (3,4-dihydro-2,2-dimethyl-2H-naphthol[1,2-b] pyran-5,6-dione, ARQ 501), a natural o-naphthoquinone and a major component in an ethanol extract of H. impetiginosus bark, displayed promising antitumor activity in various tumor cells (Pardee et al, 2002;Tagliarino et al, 2003;Terai et al, 2009;Tan et al, 2012) and has been tested as an antitumor drug in phase I, II, and III clinical trials in combination with other chemotherapeutic agents (Pardee et al, 2002;Bentle et al, 2007). The anticancer activity of β-lapachone may involve its catalysis by NAD(P) H:quinone oxidoreductase (NQO1, DT-diaphorase), which used NAD(P)H or NADH as an electron source to yield the two-electron reduction of β-lapachone (Pardee et al, 2002;Reinicke et al, 2005).…”
Section: Mnpces (N)mentioning
confidence: 99%